2016
DOI: 10.1002/hed.24444
|View full text |Cite
|
Sign up to set email alerts
|

Excision margins and sentinel lymph node status as prognostic factors in thick melanoma of the head and neck: A retrospective analysis

Abstract: Wider margins do not significantly improve locoregional recurrence or MSS. Sentinel lymph node involvement reflects a poor prognosis. © 2016 Wiley Periodicals, Inc. Head Neck 38: 1373-1379, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
3
4
0
Order By: Relevance
“…Most tumors in our study were ulcerated, and this feature was not associated with PFS or OS. Similar results were noted by Blakely A. et al [26], Ruskin O. et al [43], Yamamoto M. et al [45], and Gyorki D.E. et al [46], while Rodriguez Otero J.C. et al [33] and Bello D. et al [36] found ulceration to be a significant adverse prognostic factor only in univariate analysis.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Most tumors in our study were ulcerated, and this feature was not associated with PFS or OS. Similar results were noted by Blakely A. et al [26], Ruskin O. et al [43], Yamamoto M. et al [45], and Gyorki D.E. et al [46], while Rodriguez Otero J.C. et al [33] and Bello D. et al [36] found ulceration to be a significant adverse prognostic factor only in univariate analysis.…”
Section: Discussionsupporting
confidence: 81%
“…However, these findings were not confirmed by multivariate analyses. These results concord with some studies about thick cutaneous melanomas [26,41,43,44]. On the contrary, other authors demonstrated that mitotic rate is associated with progressive disease and decreased OS.…”
Section: Discussionsupporting
confidence: 81%
“…There were no differences in disease‐free survival and local recurrence between the two groups. In contrast, another single‐center study on T4 CMHN found a high rate of locoregional recurrence (27%), but margins ≥2 cm failed to offer any benefit in recurrence rates or MSS 3 …”
Section: Literature Reviewmentioning
confidence: 87%
“…In contrast, another single-center study on T4 CMHN found a high rate of locoregional recurrence (27%), but margins ≥2 cm failed to offer any benefit in recurrence rates or MSS. 3 Alternative techniques to WLE such as Mohs micrographic surgery (MMS) and staged excision (SE) have gained acceptance due to their reliance on histopathologic rather than clinical margins. MMS and SE allows for comprehensive margin assessment which can be utilized for tumors with clinically ill-defined margins in sensitive locations such as the lip and peri-ocular area.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Three low-quality retrospective cohort studies were identified to directly inform this recommendation for invasive (pT1-pT4) melanoma. All three reviewed the medical records of patients diagnosed with melanoma located on the head and neck and found no difference in survival rates [21][22][23] or recurrence rates 22,23 when margins of different sizes were compared.…”
Section: Key Evidence and Interpretationmentioning
confidence: 99%